Efektivitas Model Pembelajaran Problem Solving dengan Teori Bruner terhadap Hasil Belajar Siswa Kelas VII Materi Pecahan - Defy Indrasari; Ketut Sarjana; Arjudin Arjudin; Hapipi Hapipi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This research aims to find out the effectiveness of the Problem Solving learning model with Bruner Theory on students’ learning outcomes in the fraction material of 7th grade of SMP Negeri 2 Madapangga academic year 2020/2021. This research uses a quasi experiment type with the posttest only design with nonequivalent groups. The sampling technique in this research is cluster random sampling technique with class VII-A as the experimental class and class VII-B as the control class. In the experimental class, the Problem Solving learning model was applied with Bruner's Theory and the control class applied a conventional learning model. The instrument used is a learning outcome test (post-test). The quantity analysis was used t-test obtained that the Problem Solving learning model with Bruner’s theory is effective to increase the student results of 7th grade on fractions material in SMP Negeri 2 Madapangga academic year 2020/2021.